Pupillometry in the Emergency Department: A Tool for Predicting Patient Disposition - Gonzalez, Hector; Chen, Yanying; Addo, Newton; Madhok, Debbie Y. (The western journal of emergency medicine, 2025)
Objectives: To evaluate the prognostic capability of the Neurological Pupil Index (NPI) in predicting patient disposition from within the emergency department (ED). Method: This prospective observational study followed fifty comatose patients (Glasgow Coma Scale score < 9) treated in the ED at a Level 1 Trauma Center and public safety net hospital located in San Francisco, CA. NPI scores were calculated using the NPi®-200 pupillometer. Data on patient demographics, clinical characteristics, and outcomes were collected. NPI scores were categorized into three groups: 0 (very poor), 0.1-3.0 (poor to moderate), and 3.1-5.0 (good). ANOVA, Pearson’s Chi-squared test, Wilcoxon rank sum test, and Fisher’s exact test, were used to assess the association between NPI scores and discharge status. Results were reported as odds ratios with 95% confidence intervals, with a p-value < 0.05 considered statistically significant. Results: The median age of patients in this study was 58 years (IQR: 42-74), and 66% were male. Higher NPI scores (3.1-5) were significantly associated with an increased likelihood of ED discharge (81%), while lower NPI scores (0) were predominantly associated with hospital admission (92%) (p < 0.001). Significant predictors of discharge status included patient age, GCS scores, and coma etiology. Conclusions: This study highlights the utility of the NPI, a reliable and objective measure, in predicting patient disposition from within the ED. Higher NPI scores were strongly associated with an increased likelihood of ED discharge. These findings support the idea that NPI has the potential to enhance the accuracy of prognostic assessments, in comparison to subjective characterizations of pupil activity. Additional research with larger, multicenter cohorts is recommended to confirm these results and establish standardized protocols for integration of NPI in ED workflow.